COL12A1 rs970547 Polymorphism Does Not Alter Susceptibility to Anterior Cruciate Ligament Rupture: A Meta-Analysis - Lv, Zheng-tao; Wang, Wei; Zhao, Dong-ming; Huang, Jun-ming (Frontiers in Genetics, 2021)
Objective: Currently available evidence regarding the relationship between collagen type XII α1 (COL12A1) polymorphism and risk of anterior cruciate ligament rupture (ACLR) remains elusive. The aim of our present study was to assess the association between rs970547 of COL12A1 gene and ACLR risk. Methods: Five online databases included PubMed, EMBASE, ISI Web of Science, CENTRAL and CNKI were searched from their inception data up to December 2020 to identify relative observational studies. The methodological quality of each individual study was evaluated using the Newcastle-Ottawa Scale (NOS). The “model-free approach” was employed to capture the genetic effect of COL12A1 polymorphism on ACLR risk, and the association was expressed using odds ratio (OR) and its associated 95% confidence interval (95%CI). Subgroup analysis was performed according to ethnicity and gender of included subjects. Results: Eight studies involving 1477 subjects with ACLR and 100439 healthy controls were finally included in our study. The “model-free” approach suggested that rs970547 was not associated with risk of ACLR but we still used the allele model to present the combined data. Under random-effect model, rs970547 was not associated with ACLR (OR: 0.91, 95%CI 0.77, 1.08; P=0.28). Stratified analysis by gender and ethnicity also suggested no association. Conclusion: The findings of this current meta-analysis suggested that rs970547 was no associated with ACLR risk in male, female and the overall population among Asian or Caucasian.